Reliability and validity of functional grip strength measures across holds and body positions in climbers: Associations with skill and climbing performance - van Bergen, N. G.; Soekarjo, K.; Van der Kamp, J.; Orth, D. (Research Quarterly for Exercise and Sport, 2023)
Purpose In climbing, exceptional levels of fingertip strength across different holds and body positions are considered essential for performance. There is no commonly agreed upon way to measure such "grip strength variability." Furthermore, the accurate and reliable monitoring of strength is necessary to achieve safe, progressive improvement in strength. Therefore, this study aimed to develop reliability and criterion validity for assessment of grip strength across multiple holds and body positions.